2019
DOI: 10.31211/rpics.2019.5.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do sono e sonolência em estudantes do ensino superior

Abstract: Objetivos: O sono ao demonstrar-se fundamental para o desenvolvimento do indivíduo, despertando o interesse em investigar qualidade do sono em estudantes do ensino superior. Assim, pretendeu-se com o presente estudo, caracterizar as componentes da qualidade subjetiva do sono e sonolência excessiva diurna numa amostra de estudantes do ensino superior. Método: Aplicaram-se as versões portuguesas do Índice da qualidade do sono (PSQI-PT) e da Escala de Sonolência excessiva diurna (ESS), em 257 estudantes do ensino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
2
7
0
5
Order By: Relevance
“…Participants were primarily women (78.2%), with an average of 23 years old. The majority do not have a dating relationship, as reported previously in similar samples (Ariño & Bardagi, 2018;Mendes et al, 2019). However, we found a smaller percentage of women and mean age higher than in earlier studies (e.g., Sequeira et al, 2019;88.6% women, 21 years and by Roldán-Merino et al, 2017;87% women, 21.5 years).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Participants were primarily women (78.2%), with an average of 23 years old. The majority do not have a dating relationship, as reported previously in similar samples (Ariño & Bardagi, 2018;Mendes et al, 2019). However, we found a smaller percentage of women and mean age higher than in earlier studies (e.g., Sequeira et al, 2019;88.6% women, 21 years and by Roldán-Merino et al, 2017;87% women, 21.5 years).…”
Section: Discussionsupporting
confidence: 58%
“…Some variables seem to be students' psychological well-being predictors, like male gender, dating relationship, good academic performance, exercise, sleeping 7 h per night, and academic life satisfaction (Nogueira & Sequeira, 2020). Evidence shows that exercise, the quality of sleep, and a healthy diet are strong predictors of HES well-being (Bartonicek et al, 2020;Collins et al, 2020;Mendes et al, 2019). Good night's sleep is essential for a person's well-functioning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies showed that sleep disturbances and deprivation predict distress and are associated with psychological symptoms and depression (24); students' sleep quality worsens during high-stress periods (6, 11); sleep quality and mental health levels improve with regular physical exercise (10,39). This knowledge is noteworthy and particularly relevant for health professionals to diagnose sleep-related disorders and poor sleep quality to implement accurate educational programs that empower students to adopt healthier sleep hygiene patterns and behaviours on campus (11,40,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…O sono é um processo fisiológico e psicológico complexo, de natureza cíclica e reversível, sendo essencial para o funcionamento do sistema nervoso central (SNC) e para a saúde física e mental dos indivíduos (Souza et al, 2013;Carvalho et al, 2013;Mendes et al, 2019). Segundo a National Sleep Foundation (NSF), é essencial que os adultos entre 18 e 64 anos durmam entre 7 e 9 horas por noite.…”
Section: Introductionunclassified